2012
DOI: 10.3846/16487788.2012.753679
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hysteresis in Axial Compressors of Gas-Turbine Engines

Abstract: The phenomenon of separated flow hysteresis in the process of the streamlining the axial compressor of gas-turbine engines is considered. Generalised results of research on the occurrence of hysteresis in the aerodynamic performance of compressor grids and its influence on the performance of the bladed disks of compressors that operate in real conditions of periodic circular non-uniformity are demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Zheng proposed a reasonable tolerance allocation strategy based on the joint game theory, which found a balance point for each assembly component to weigh the assembly cost and assembly quality [11]. For rotationally symmetrical aero-engine components, to control the tolerance transfer process in the assembly process, Klocke proposed a set of intelligent assembly system, which can realize the automatic distribution of disklike components with the center as the installation reference and meet certain tolerance requirements [12][13][14].…”
Section: Quick Browse and Highlightmentioning
confidence: 99%
“…Zheng proposed a reasonable tolerance allocation strategy based on the joint game theory, which found a balance point for each assembly component to weigh the assembly cost and assembly quality [11]. For rotationally symmetrical aero-engine components, to control the tolerance transfer process in the assembly process, Klocke proposed a set of intelligent assembly system, which can realize the automatic distribution of disklike components with the center as the installation reference and meet certain tolerance requirements [12][13][14].…”
Section: Quick Browse and Highlightmentioning
confidence: 99%
“…Their work showed that if the velocity of the gas entering the chamber increases (To a certain extent), the efficiency of the straight VT cyclone separator can be improved. The separated flow hysteresis phenomenon in the process of the streamlining the gas-turbine engines axial compressor is analyzed by Kulyk et al (2012). The accuracy of different turbulence models in prediction of separation phenomenon has been analyzed by Rafiee and Sadeghiazad (2016b).In order to increase the energy separation rate and the thermal efficiency, and optimize the dimensions of the straight VT cyclone separator system, thereby decreasing the operating costs, the geometrical optimization techniques are usually applied.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%
“…Furthermore, in the assembly of propellant tanks in spacecraft, gas turbines and aero-engine components, most parts are rotationally symmetric cylindrical components (Griffin et al, 2003;Kulyk et al, 2012;Papastathis et al, 2010). To control the tolerance propagation in the assembly of cylindrical components, much work had been done.…”
Section: Introductionmentioning
confidence: 99%